Characteristics and Readiness of Oil Palm Households for Replanting Program: Is an Empowerment Program Needed? - Novra, Ardi; Yogaswara, Adriani; Abubakar, Fatati (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
This article describes a new idea of how the level of intervention in household empowerment policies is based on an empirical study of the magnitude of the negative impact of the smallholder palm oil replanting (SPR) program. One of the negative impacts of this program is the temporary loss of income (TLI) for farmer households due to the cessation of production of oil palm fruit bunches. The household survey research was conducted in three village centers for smallholder oil palm plantations in Jambi Province, Indonesia. The research result shows that the average potential TLI in each household if replanting palm oil is carried out is IDR 2,364,644/ month (equivalent to 74.55% of the oil palm household income or 39.78% of the regional economy), Purwodadi Village is the village most vulnerable to regional economic disturbances due to the high potential for TLI, reaching 99.43% of the oil palm household income and 67.06% of the regional economy. The level of TLI is influenced by factors of age and area of old oil palm plants, the proportion of households that will undergo the replanting process, and the level of dependence of regions on oil palm. Based on the results of the research, it can be concluded that there is still a need for innovation and expansion of empowerment to encourage household readiness in facing the SPR program.